Pemakaian Variasi Bahasa Slang pada Anak Jalanan di Kawasan Taman Kota Ajibarang - Setyawan, Irgi; Permadi, Deni; Setyorini, Ririn (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The purpose of this study is to describe vocabulary in the variation of slang language used by street children in Ajibarang Cit Park Area and the form of sentences on the use of slang language variations in street children in the Ajibarang City Park Area. This study employed qualitative methods. Sources of data in this study were notes and recordings obtained from interviews with groups of street children. The data were collected by using the method of listening, taking note, recording and interviewing street children in the Ajibarang City Park area. Data collection was carried out on 20-21 June 2021 in the Ajibarang City Park Area, by interviewing several street children who were in the area. The results of the study found 12 vocabularies of slang variations used by street children in the Taman Kota Ajibarang area, including: Gaber, Bacot, Cod, Gas, Oi oi, Sebats, Gercep, Al men, Cok, Badog, Dog, Komuk and sentences from the results of research on variations of slang by street children in Ajibarang City Park.